1998
DOI: 10.1007/pl00005298
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of individual cytochrome P450 enzymes involved in the metabolism of clozapine

Abstract: The atypical antipsychotic clozapine has been reported to be metabolised mainly to its N-oxide and N-demethylated products. In the present study, individual recombinant cytochrome P450 (CYP) and flavin-containing monooxygenase (FMO) enzymes were used to elucidate which enzymes are responsible for these metabolic conversions. In vitro metabolism of clozapine was investigated using human CYP1A1, CYP1A2, CYP2C8, CYP2E1, CYP2C9-arg144, CYP2C9-cys144, CYP2C19, CYP2D6, CYP3A4, CYP3A5 and FMO3 supplemented with an NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 22 publications
1
56
1
2
Order By: Relevance
“…Incubations with recombinant human P450 were performed at CLZ concentrations of 10 and 100 mM, as was done previously Eiermann et al, 1997;Linnet and Olesen, 1997;Fang et al, 1998;Tugnait et al, 1999;Olesen and Linnet, 2001;Zhang et al, 2008;Dragovic et al, 2010). Duplicate incubations were performed in 100 mM potassium phosphate buffer (pH 7.4) at a final volume of 200 ml.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Incubations with recombinant human P450 were performed at CLZ concentrations of 10 and 100 mM, as was done previously Eiermann et al, 1997;Linnet and Olesen, 1997;Fang et al, 1998;Tugnait et al, 1999;Olesen and Linnet, 2001;Zhang et al, 2008;Dragovic et al, 2010). Duplicate incubations were performed in 100 mM potassium phosphate buffer (pH 7.4) at a final volume of 200 ml.…”
Section: Methodsmentioning
confidence: 99%
“…CYP1A2) and N-oxidation (CYP3A4 . CYP1A2, CYP2D6) of CLZ, whereas the other P450s showed only low or no activity Eiermann et al, 1997;Linnet and Olesen, 1997;Fang et al, 1998;Tugnait et al, 1999;Olesen and Linnet, 2001;Zhang et al, 2008). Figure 4 shows the relative activities of individual recombinant human P450s in bioactivation of CLZ using GSH and potassium cyanide as trapping agents.…”
Section: Bioactivation Of Clozapine By Human P450s 653mentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacokinetic data showed that coadministration of GA significantly lowered concentrations and exposure of norCLZ and CLZ Noxide, indicating that formations of norCLZ and CLZ Noxide were inhibited by GA, which were verified by data on hepatic microsomes and hepatocytes of rats. CLZ metabolism in human liver was reported to be mainly mediated by CYP1A2, CYP3A4, CYP2C19, CYP2C9, and CYP2D6 (5), although FMO also contri buted to formation of CLZ Noxide (6,7). Activities of CYP450s in hepatic microsomes of rats were measured using corresponding substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, other CYP isoenzymes such as 3A4, 2D6, 2C9, 2C19, 2E1 have also been implicated in the drug's metabolism, Troostwijk et al 2003;Fang et al 1998;Ozdemir et al 2001;Taylor 1997;Wetzel et al 1998]. In vitro data suggest that other CYPs which are also involved in the formation of norclozapine are 2C19 and 3A4, with the latter also being the main enzyme mediating the formation of clozapine N-oxide [Eiermann et al 1997;Olesen and Linnet 2001].The importance of 2D6 has been questioned by many as no difference in clozapine's metabolite generation has been seen in 2D6 ultra-rapid metabolizers compared with slow metabolizers [Dahl et al 1994].…”
Section: Clozapine Metabolismmentioning
confidence: 99%